OPTIMALISASI RANTAI PASOK DENGAN MENINGKATKAN DAYA SAING UMKM DI KOTA SUKABUMI - Shamsudin, Alsya Nurliza; Jahriyah, Nabila; Alhidayatullah, Alhidayatullah (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
This study aims to explore the application of Supply Chain Management (SCM) principles in increasing the competitiveness of MSMEs in Sukabumi City by identifying relevant performance indicators in designing new products and analyzing factors that affect MSME operational performance, such as production cycle time, capacity utilization, product quality, and customer satisfaction. Using a qualitative method with a descriptive approach, data was collected through interviews, observations, and documentary studies of five MSMEs, where the data analysis techniques obtained used source and time triangulation. The results of the study show that efficiency in the supply chain, optimization of production capacity, and improvement of product quality contribute greatly to the competitiveness of MSMEs, while the lack of innovation and process improvement is still the main challenge. Therefore, this study recommends the application of technology in SCM, improvement of human resource skills, closer collaboration with suppliers and distributors, and stronger policy support to support the sustainability and competitiveness of MSMEs.